Persepsi Konsumen Terhadap Prioritas Perbaikan Infrastruktur Pasar Tradisional (Studi Kasus : Pasar Perumnas Klender) - Siregar, Bernardhus Wishman (UI Scholars Hub, 2014)
everal studies have found that consumer in Indonesia has shifted their preference from traditional to modern market, due to a better service provided by modern market retailer for its consumer. Focusing on consumer perceptions, this research tries to see the consumer assessment for traditional market's service and infrastructures using the gualitative approach in Pasar Perumnas Klender. Finally, this research found that improvements in infrastructure is necessary in order to meet the consumer needs.